Аналіз аварійних режимів роботи вимірювальних трансформаторів струму - Яцейко, Андрій; Ференсович, Роман (Видавництво Львівської політехніки, 2013)
Disconnecting the secondary circuits from current transformers are accompanied by the occurrence on the terminals of their secondary windings surges which are dangerous for isolation of current transformers, attached to them equipment and life staff. The paper analyzes emergency modes of working two-stage current transformer type TFZM-500 after disconnecting secondary windings its stages. Researches were conducted on created in computer program design scheme of this cascade transformer which allows to model various modes of its working. Results of investigation have theoretical and practical significance for further analysis modes of disconnecting secondary circuits of current transformers in order to create effective and reliable methods of protecting from surges. It is shown a block diagram of current transformer protection system from action of dangerous surges after disconnecting its secondary circuits which based on using microprocessor technology.
Keywords: трансформатор струму; обмотка; високо-вольтний імпульс; перенапруга; розмикання; осцилограма